17‐β estradiol attenuates the pro‐oxidant activity of corticotropin‐releasing hormone in macroendothelial cells. (23rd June 2019) - Filiponi, Maria; Gougoura, Sofia G; Befani, Christina; Bargiota, Αlexandra; Liakos, Panagiotis; Koukoulis, George N
Abstract: Corticotropin‐releasing hormone, which is the predominant regulator of neuroendocrine responses to stress, attenuates inflammation through stimulation of glucocorticoid release. Enhanced corticotropin‐releasing hormone expression has been detected in inflammatory cells of the vascular endothelium, where it acts as a local regulator of endothelial redox homeostasis. Estrogens have beneficial effects on endothelial integrity and function, though the mechanism underlying their antioxidative effect remains as yet largely unknown. We therefore investigated the effect of 17β‐estradiol on pro‐oxidant action of corticotropin‐releasing hormone in vitro in macroendothelial cells, and, more specifically, the role of 17β‐estradiol on corticotropin‐releasing hormone‐induced activities/release of the antioxidant enzymes namely, endothelial nitric oxide synthase, superoxide dismutase, catalase, and glutathione. We observed that 17β‐estradiol abolished the stimulatory effect of corticotropin‐releasing hormone on intracellular reactive oxygen species levels and counteracted its inhibitory effect on endothelial nitric oxide synthase activity and nitric oxide release. In addition, 17β‐estradiol significantly induced superoxide dismutase and catalase activity, an effect that was not significantly influenced by corticotropin‐releasing hormone. Finally, 17β‐estradiol significantly increased glutathione levels and the glutathione/glutathione + glutathione disulfide ratio, an action that was partially blocked by corticotropin‐releasing hormone. Our results reveal that 17β‐estradiol counterbalances corticotropin‐releasing hormone‐mediated pro‐inflammatory action and thereby maintains the physiological threshold of the endothelial cell redox environment. These observations may be of importance, considering the protective role of estrogen in the development of atherosclerosis.